The influence of the 2030 Agenda on sustainable consumption through an analysis of academic publications - Barbosa , Alan Marcelo; Branchi, Bruna Angela; Ferreira , Denise Helena Lombardo (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
The sustainable development in a society depends on different factors, among which we can highlight the consciousness of the inhabitants about the need to maintain habits and consumption standards aligned with concepts of sustainability to ensure the preservation of natural resources for current and future generations. Focusing on the theme of consumption standards, this study aims to assess the influence of fostering the 2030 Agenda in academic publications related to the sustainable consumption theme. This research is classified as a bibliometric analysis, as it seeks to quantify the scientific production and its dissemination, with a quantitative approach, as it measures what was observed. The SCOPUS and SciELO databases were selected for the bibliometric research, with consultations on 06/23/2021. The results show that the articles available in the SCOPUS database represents 97.3% of publications with the term “sustainable consumption”. After 2015, the year of the introduction of the 2030 Agenda, there was an accelerated growth of the term Sustainable Consumption in academic publications, especially in the English language.